Design, Synthesis, and Antifouling Activity of Glucosamine-Based Isocyanides - Umezawa, Taiki; Hasegawa, Yuki; Novita, Ira; Suzuki, Junya; Morozumi, Tatsuya; Nogata, Yasuyuki; Yoshimura, Erina; Matsuda, Fuyuhiko (Marine drugs, 2017)
Biofouling, an undesirable accumulation of organisms on sea-immersed structures such as ship hulls and fishing nets, is a serious economic issue whose effects include oil wastage and clogged nets. Organotin compounds were utilized since the 1960s as an antifouling material; however, the use of such compounds was later banned by the International Maritime Organization (IMO) due to their high toxicity toward marine organisms, resulting in masculinization and imposex. Since the ban, there have been extensive efforts to develop environmentally benign antifoulants. Natural antifouling products obtained from marine creatures have been the subject of considerable attention due to their potent antifouling activity and low toxicity. These antifouling compounds often contain isocyano groups, which are well known to have natural antifouling properties. On the basis of our previous total synthesis of natural isocyanoterpenoids, we envisaged the installation of an isocyano functional group onto glucosamine to produce an environmentally friendly antifouling material. This paper describes an effective synthetic method for various glucosamine-based isocyanides and evaluation of their antifouling activity and toxicity against cypris larvae of the barnacle Amphibalanus amphitrite. Glucosamine isocyanides with an ether functionality at the anomeric position exhibited potent antifouling activity, with EC50 values below 1 μg/mL, without detectable toxicity even at a high concentration of 10 μg/mL. Two isocyanides had EC50 values of 0.23 and 0.25 μg/mL, comparable to that of CuSO4, which is used as a fouling inhibitor (EC50 = 0.27 μg/mL).